If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + -3x) + 4 = -6(-8 + 2x) + -2 (3 * 2 + -3x * 2) + 4 = -6(-8 + 2x) + -2 (6 + -6x) + 4 = -6(-8 + 2x) + -2 Reorder the terms: 6 + 4 + -6x = -6(-8 + 2x) + -2 Combine like terms: 6 + 4 = 10 10 + -6x = -6(-8 + 2x) + -2 10 + -6x = (-8 * -6 + 2x * -6) + -2 10 + -6x = (48 + -12x) + -2 Reorder the terms: 10 + -6x = 48 + -2 + -12x Combine like terms: 48 + -2 = 46 10 + -6x = 46 + -12x Solving 10 + -6x = 46 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 10 + -6x + 12x = 46 + -12x + 12x Combine like terms: -6x + 12x = 6x 10 + 6x = 46 + -12x + 12x Combine like terms: -12x + 12x = 0 10 + 6x = 46 + 0 10 + 6x = 46 Add '-10' to each side of the equation. 10 + -10 + 6x = 46 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = 46 + -10 6x = 46 + -10 Combine like terms: 46 + -10 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 6x^2+7xy+3y^2=144 | | 5log+10=7m | | -8(1-x)=64 | | x-50=16 | | 3b-9-8b=8 | | 2000=-4p^2+60p+1039 | | -4n+6=3n+8+4 | | 3(.9-t)=-5(16+3t) | | 9x-2x+8=3x+38+y | | 5log=-10-7m | | 14+7c=14c+28 | | (7-2)-(-3t+1)=-3(1-3t) | | 12yards= | | 28=5+6x | | 5/3a-4/3a=1/12 | | -367x=-139 | | (2x-6)+(2x-6)+(x+3)+(x+3)=24 | | 5(x+3)-2=2-1x+9 | | 50=2(15+w) | | x+4x+3x+2x=144 | | -9x+27=-45 | | -12x-(-4)+8x=12x | | 2a-4=3a-5 | | 7n=-2m+10 | | 6x^2+4x-14=0 | | (x+6)+(5x)+(3x+3)=4(x+6) | | 29=x-168 | | 4p-3forx=3 | | 3(-5.4n+1)+5.6n=26.5 | | 2x+5+5x=-12 | | =84 | | 5log-7m+4=-6 |